Getting away with torture: secret government, war crimes, and the rule of law - Pyle, Christopher H. (Potomac Books, 2009)
A policy of torture -- Unleashing the dogs of war -- Torture by proxy -- Signaling permission -- Covering up -- The war criminals -- Torture reconsidered -- Congress : the enablers -- Judicial complicity -- Why do they hate our freedoms? -- Restoring the rule of law